Passive dosimetry of electron irradiated borosilicate glass slides - Sani, S.F. A.; Othman, M.H.U.; Alqahtani, A.; Nazeri, A.A.Z. A.; Almugren, K.S.; Ung, N.M.; Hashim, S.A.; Alkallas, F.H.; Bradley, D.A. * (Elsevier, 2021)
Thermoluminescence dosimetry most typically concerns the sensing and quantification of ionizing radiation exposures, with evaluation of absorbed dose arising from electron-hole trapping in well-disposed insulating/semi-conducting media. In this passive form of dosimetry the signal derives from photons released post-irradiation heating of the dosimeter over a specific temperature range. Herein, for entrance doses from 2 Gy up to 250 kGy, investigation is made of the thermoluminescence properties of electron irradiated borosilicate glass (SiO2–B2O3), the samples deriving from commercial microscope slides (coverslips) of thickness 1.0 mm. The coverslips provide linear TL response over a wide range of radiation dose, through use of a clinical linear accelerator in a lower dose regime (2–10 Gy) and use of a product-irradiation electron linac in a higher dose regime (25 kGy–250 kGy), obtaining a regression coefficient in excess of 96%. In the high dose regime comparison has been made with the response of Ge–B doped Flat Fibre (FF) and Ge–B doped photonic crystal fibre (PCF) (collapsed). Deconvolution shows the glow curves of the borosilicate glass to be formed of five overlapping peaks, with figures of merit (FOM) of between 0.62 – 1.72 and 0.87–1.00 for the particular dose ranges 2–10 Gy and 25 kGy–250 kGy respectively. Through use of Glowfit deconvolution software, the key trapping parameters of activation energy and frequency factor were calculated for the borosilicate glass slide.